The utopia and metaphysics of time in Jorge Luis Borges’ "Tlön, Uqbar, Orbis Tertius" - Amado Cano, José David (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
This article examines Borges’ short story «Tlön, Uqbar, Orbis Tertius» and compares it with several Utopian texts. It focuses on the configuration of narrative time in the imaginary world of Tlön, following Augustine of Hippo’s and Paul Ricoeur’s philosophies. The analysis of the metaphysical theories of time, and how Tlönians perceive and experience it, allows us to talk about Tlön as a living metaphor of our world.